Phonology in text messages - Kul, Małgorzata (Versita, 2007)
Text messages operate on a protocol which allows from 148 to 160 characters per message, including spaces between words. In such a highly circumscribed environment, writing is seriously hampered by the limited space and the usage of the numeric phone keypad. Thus, the advent of a new quality of the text language, sometimes referred to as ‘textese’, was inevitable under those conditions. One of the characteristics of text messages is frequent deletion of letters in orthographical forms, like in the following example: IfYaMthWozNEBiGrUWdntHavNEFAcLft2Wsh (if your mouth was any bigger you wouldn't have anything else left to wash). In order to investigate the nature of letter deletions in text messages a study was undertaken, which analyzed ten examples of text messages coming from various sources (the sources are listed in the references, whereas the examples are listed in Appendix). The aim of the study was to determine whether the deletion of letters was regular, the general prediction being that text messages are decoded via the mediation of their phonemic representations (or via mental reading). It was speculated that the regularities were governed by phonological principles such as the semiotic ‘figure and ground’ principle (Dressler 1996) and the ‘rich-get-richer’ principle (Donegan 1978/1985). The results demonstrate that phonology is very likely to govern reductions albeit without any recourse to the prosody level. More specifically, phonology apparently affects the pattern of deletions in text messages, whereas there is a marked tendency that stress assignment does not determine the nature of deletions. The paper is organized in the following way: first, the linguistic literature on text messages is briefly reviewed. Next, the study is described in terms of data and procedure. Then, the results are presented and discussed. Finally, conclusions and suggestions for further research are outlined.
Keywords: Text messages